Pengaruh Langsung dan Tidak Langsung Person Job Fit terhadap Kinerja Pegawai dengan Komitmen Afektif sebagai Mediating pada Dinas Komunikasi dan Informatika Kota Madiun - Sunardi, Sunardi; Srimulyani, Veronika Agustini (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2020)
This study aims to prove empirically that person job fit has direct and indirect effects on employee performance with affective commitment as an intervening to the employees of the Communication and Information Office of Madiun City. The samples in this study was 44 employees of the Communication and Information Office of Madiun City. The sampling technique in this study uses the saturated sample method. Hypothesis testing uses multiple linear regression analyses with the help of the SPSS 22 program and path analysis. The results showed that person job fit directly had a significant positive effect on employee performance, person job fit had a significant positive effect on affective commitment, affective commitment had a significant positive effect on employee performance, and person job fit indirectly affected employee performance through affective commitment as partial mediating.